DEVELOPMENT OF SCIENCE TEST TO MEASURE HOTS AND DIGITAL LITERACY OF JUNIOR HIGH SCHOOL STUDENTS ON THE TOPIC OF CITY NOISE - Nurwahidah, Indri; Widiyawati, Yeni; Sari, Dwi Septiana; Masykuri, Mohammad; Budiyanto, Cucuk Wawan (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2020)
PENGEMBANGAN SCIENCE TEST UNTUK MENGUKUR HOTS DAN DIGITAL LITERACY SISWA SMP PADA TEMA KEBISINGAN KOTAÂ AbstractThe 2013 Curriculum emphasizes the process to improve HOTS and digital literacy. However, no appropriate science test instrument can measure the combination of these two aspects in contextual topics and relate to real-world problems. This kind of science test will engage students in-depth thinking as well as improve their digital literacy. This research aims to develop science tests based on HOTS and digital literacy in the City Noise theme for 8th-grade students. HOTS is operationally defined as critical thinking, creativity, collaboration, and communication (4C), while digital literacy is a thinking and operation skill. Borg & Gall models were adopted in this research and development. A total of 21 private school students in Semarang were subject to this research and investigated the validity and reliability of developed science tests. Based on expert judgment, the science test instrument, which consists of 25 multiple choice items and five essay items, was in a very good category. Based on the Rasch model analysis, the science tests are valid (28 items are valid) and reliable (Alpha cronbach=0.79). It can be concluded that the developed science test is feasible to use to measure HOTS and digital literacy of junior high school students on the topic of the City Noise.AbstrakKurikulum 2013 menekankan pada proses peningkatan HOTS dan digital literacy. Namun, belum banyak tersedia instrumen tes sains yang mampu mengukur kombinasi dari kedua aspek tersebut dalam topik yang kontekstual dan berhubungan dengan masalah nyata. Jenis science test seperti ini dapat melibatkan siswa dalam proses berpikir mendalam serta dapat meningkatkan digital literacy. Tujuan dari penelitian ini yaitu mengembangkan science test berbasis HOTS dan digital literacy pada tema Kebisingan Kota untuk siswa kelas 8. HOTS secara operasional didefinisikan sebagai critical thinking, creativity, collaboration and communication (4C) sementara digital literacy sebagai thinking skills dan operation skills. Penelitian ini merupakan penelitian pengembangan (R&D) yang mengadaptasi dari Borg & Gall. Sebanyak 21 siswa dari SMP swasta di Semarang digunakan sebagai subjek dalam penelitian ini dan digunakan untuk mengetahui validitas dan reliabilitas science test hasil pengembangan. Berdasarkan hasil validasi ahli, instrumen science test yang terdiri dari 25 item pilihan ganda dan 5 item uraian termasuk dalam kategori baik. berdasarkan hasil analisis Rasch model, science test dikatakan valid (28 item valid) dan reliabel (Alpha Cronbach=0,79). Dengan demikian dapat disimpulkan bahwa science test hasil pengembangan layak digunakan untuk mengukur HOTS dan digital literacy siswa SMP pada tema Kebisingan Kota. Â